2011 IEEE Nuclear Science Symposium Conference Record 2011
DOI: 10.1109/nssmic.2011.6153812
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of the image space reconstruction algorithm

Abstract: The image space reconstruction algorithm (ISRA) has been shown to be a non-negative least squares estimator, and was introduced as an alternative iterative image reconstruction method for positron emission tomography (PET) data. The implementation of ISRA is straightforward: the ratio of the backprojected measured data to that of the backprojected expected data is used to multiplicatively update the current image estimate. This work starts with a modified weighted least squares objective function to derive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The MLEM is presented as a particular case of RAMLA. In [221], both ISRA and MLEM were presented from the point of view of a gradient descent algorithm of a weighted least-squares objective function, with properly chosen descent steps. In terms of noise models, the weighted least squares can be viewed as the log-likelihood of a gaussian model of the noise.…”
Section: Iterative Methodsmentioning
confidence: 99%
“…The MLEM is presented as a particular case of RAMLA. In [221], both ISRA and MLEM were presented from the point of view of a gradient descent algorithm of a weighted least-squares objective function, with properly chosen descent steps. In terms of noise models, the weighted least squares can be viewed as the log-likelihood of a gaussian model of the noise.…”
Section: Iterative Methodsmentioning
confidence: 99%
“…Variants of this algorithm were used to correct early Hubble Space Telescope images for aberrations resulting from the improper figure of the primary mirror [Hanisch et al, 1997]. A second ISRA, which we call the Least Squares Positive Definite (LSPD) algorithm, has been discovered independently by several researchers [Reader et al, 2011;Jansson, 1997;Gold, 1964], and the authors, although we have not found this algorithm, has a specific name in the literature. The RL algorithm is designed to handle measurements that follow the Poisson distribution, while the LSPD algorithm is tailored to measurements that follow the normal distribution.…”
Section: 1002/2015rs005869mentioning
confidence: 99%
“…In this work, the optimization is done with a modified nonnegative least-square estimator, the ISRA. [10][11][12] In the first step, the PSF is updated by applying the ISRA E Q -T A R G E T ; t e m p : i n t r a l i n k -; s e c 2 . 1 ; 3 2 6 ; 3 6 9…”
Section: Spatially Invariant Algorithmmentioning
confidence: 99%